Evaluation of the one-step Lumicyano™ used in the visualisation of fingermarks on fabrics. Issue 5 (September 2019) - Beerman, Nicole; Savage, Anne; Dennany, Lynn; Fraser, Joanna
Abstract: This study consisted of three parts to evaluate the performance of Lumicyano™ on a variety of fabrics. One part assessed the impact of dye percentage (8%, 9% and 10%) on visualisation of fingermark detail and luminescent brightness in split grab marks. A 9% dye produced the highest quality detail of grab impressions with least interference from background fluorescence. The second part investigated the optimal relative humidity (RH, 75–84%) for certain fabric types using Lumicyano on split, six-series depletion fingermarks. It was concluded that the recommended RH of 80% remained the ideal cyanoacrylate fuming environment. The final and third part of this study determined the impact of sequential addition of Basic Yellow 40 (BY40) on Lumicyano compared to traditional cyanoacrylate (CA) followed with BY40 application. Results from this study demonstrated that Lumicyano on its own developed fingermarks with superior quality to Lumicyano with sequential addition of BY40 or traditional cyanoacrylate followed by BY40. Inclusion of more fabrics, donors and longer ageing periods should be explored in future studies to determine what frameworks are best for certain types of fabrics. Highlights: Nine percent Lumicyano is the optimal dye percentage for developing and visualising fingermarks. Lumicyano is a superior method for fingermark visualisation than the traditional two-step method. A one-step Lumicyano application on fabrics performs better than as a two-step process. Sequential addition of Basic Yellow 40 is generally not recommended on the use of fabrics.